The impact of site location on the rental and open market values of commercial property using spatial analysis technique - Alias, Buang; Sipan, Atan @ Ibrahim; Eboy, Oliver Valentine (Faculty of Geoinformation Science and Engineering, 2007)
In this study several statistical techniques were used. This include Multiple Regression Model, Neural Network and ANN Model, Spatial Analysis Model such as Buffer Analysis and Geographically Weighted Regression Model. This study also identified the advantage and disadvantages of Multiple Regression, Neural Network and Spatial Analysis. Major findings from the Study are as follows i) The study also found that 17 variables such as road type, road direction, availability and proximity to car parks, schools, university, central business district, industrial area, construction site, shopping centre, sports centre, recreation centre, office area, bank, post office, bus and taxi station, and view of surrounding are significant factors in influencing the values. Proximity to police station is found to be insignificant factor in influencing values. The study found the Statistical model with in built Geographical Weighted Regression model (GWR) provides a better value prediction. . This research group is of the opinion that the GRW model should be the choice for future research to identify locational impact on property values.